Analysis of the Impact of Handover Implementation on Healthcare Quality in Inpatient Units - Husna, Novriani; Said, Faridah Binti Mohd; Nambiar, Nisha; Refti, Adinda Muethia (Journal of Neonatal Surgery, 2025)
Communication failures during the handover process are the cause of 80% of patient safety incidents in inpatient units. Analyze the impact of the implementation of the handover using the SBAR method on health service quality indicators in inpatient units. The quasi-experimental research with a pre-post test design approach involved 35 nurses for three months. Data were collected through structured questionnaires, observation sheets, and medical record documentation, then analyzed using paired t-tests and multiple regression analysis. The implementation of the SBAR protocol increased the implementation score from 45.71±2.41 to 87.46±2.03. Communication effectiveness increased from 2.46±0.51 to 4.43±0.50, patient satisfaction from 2.51±0.61 to 3.91±0.74, length of stay decreased from 5.89±0.29 days to 4.35±0.23 days, and adverse events decreased from 3.01±0.23 to 1.16±0.15 per 1000 days of treatment. All indicators showed significant differences (p<0.001) with large effect sizes. The SBAR protocol has proven to be effective in improving the quality of health services comprehensively. Permanent implementation with an ongoing training program and periodic monitoring system is recommended.